The dynamic constitution : an introduction to American constitutional law and practice - Fallon, Richard H.
"In this revised and updated second edition of The Dynamic Constitution, Richard H. Fallon, Jr., provides an engaging, sophisticated introduction to American constitutional law. Suitable for lawyers and non-lawyers alike, this book discusses contemporary constitutional doctrine involving such issues as freedom of speech, freedom of religion, rights to privacy and sexual autonomy, the death penalty, and the powers of Congress. Through examples of Supreme Court cases and portraits of past and present Justices, this book dramatizes the historical and cultural factors that have shaped constitutional law. The Dynamic Constitution, Second Edition combines detailed explication of current doctrine with insightful analysis of the political culture and theoretical debates in which constitutional practice is situated. Professor Fallon uses insights from political science to explain some aspects of constitutional evolution and emphasizes features of the judicial process that distinguish constitutional law from ordinary politics"--